2005
DOI: 10.1348/135910704x15257
|View full text |Cite
|
Sign up to set email alerts
|

Intense‐personal celebrity worship and body image: Evidence of a link among female adolescents

Abstract: Findings suggest that in female adolescents, there is an interaction between Intense-personal celebrity worship and body image between the ages of 14 and 16 years, and some tentative evidence has been found to suggest that this relationship disappears at the onset of adulthood, 17 to 20 years. Results are consistent with those authors who stress the importance of the formation of para-social relationships with media figures, and suggest that para-social relationships with celebrities perceived as having a good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
1
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 54 publications
7
117
1
10
Order By: Relevance
“…Using these criteria, 22.8% of the sample was classified as entertainment-social, 8% as intense-personal, and 2.5% as borderline-pathological. These statistics are higher than estimates among previous adult general population samples (entertainment-social, 15.1%; intense-personal, 5.1%; and borderline-pathological, 1.9%), but consistent with the view that younger people are more interested in celebrities than older adults [19]. Table 1 reports the Cronbach's alphas [30] for the multi-item scales, descriptive statistics (Means and SDs), and all the Pearson product moment correlation coefficients between all the variables.…”
Section: Descriptive Reliability and Correlational Statisticssupporting
confidence: 72%
See 1 more Smart Citation
“…Using these criteria, 22.8% of the sample was classified as entertainment-social, 8% as intense-personal, and 2.5% as borderline-pathological. These statistics are higher than estimates among previous adult general population samples (entertainment-social, 15.1%; intense-personal, 5.1%; and borderline-pathological, 1.9%), but consistent with the view that younger people are more interested in celebrities than older adults [19]. Table 1 reports the Cronbach's alphas [30] for the multi-item scales, descriptive statistics (Means and SDs), and all the Pearson product moment correlation coefficients between all the variables.…”
Section: Descriptive Reliability and Correlational Statisticssupporting
confidence: 72%
“…Such a consideration is important because research suggests a large variability in attitudebehavior consistency [18]. Furthermore, because celebrity worship and incidence of elective cosmetic surgery have associations with the same variables (e.g., body image [19]), it is necessary to examine whether any relationship between celebrity worship and the incidence of elective cosmetic surgery is maintained after controlling for several existing predictors of the incidence of elective cosmetic surgery. The aims of the current study were twofold.…”
mentioning
confidence: 99%
“…Supporting this reasoning, Maltby et al (2005) have found an association between celebrity interest for intense personal reasons and the importance they placed on body shape and weight. This relationship was shown to be agerelated, becoming apparent at 14 years but disappearing from 17 years onwards.…”
Section: Celebritymentioning
confidence: 80%
“…here is a regression from the decade 2000 to thin igure for females which is signiied attractive during that particular time, this is a negative revolution because it creates pressure on females to conform to a certain stereotype [8]. Maltby, Giles, Barber and McCutcheon agree that the regression is not natural because the media is recognized to promote unrealistic igures and glamorizing thin celebrities and models which create a considerable amount of pressure on females [13]. Over the years, females' relationship between the media stereotype of body image are conlicting and there is a constant struggle to achieve the ideal body [14].…”
Section: Body Image and Media Inluencesmentioning
confidence: 99%